Perspectives on Indian economy a collection of essays - Rangarajan, C (New Delhi UBSPD, 2000)
Perspectives on Indian economy by C.Rangarajan.The author focusses on monetary and fiscal reform,growth pattern,thedimmensions of development,the importance of technology and management and role of legislature and the judiciary ,all are covered in this bo
Keywords: Economics-India-Addreses, essays, lectures; Economic develompemnt; Economics; Monetary policy